Seismic performance of a base-isolated flexible liquid storage tank equipped with a novel rate-independent damping device. (May 2023) - Zhu, Hongping; Tang, Zian; Luo, Hao
Abstract: Conventional base-isolation systems can significantly reduce the hydrodynamic pressure on the walls of large liquid storage tanks, but they have limited or even adverse effects on the sloshing response of liquids because the sloshing period is comparable to the isolation period. In this study, a combined base-isolation system consisting of natural rubber bearings and a novel rate-independent damping device was developed to achieve a simultaneous reduction in the hydrodynamic pressures and sloshing heights of liquid storage tanks. Using an analytical flexible tank model considering higher sloshing modes, the seismic responses of liquid storage tanks equipped with the proposed combined base-isolation system under strong ground motions were investigated. The influence of tank flexibility, higher sloshing modes, and liquid heights on the seismic responses of the controlled storage tank were evaluated quantitatively. The effectiveness of the proposed combined base-isolation system was verified, and its advantages over conventional base-isolation systems were identified. The proposed system can achieve a larger reduction in base shear, overturning moment, and sloshing height than conventional systems without increasing the isolator displacements.